2020
DOI: 10.1016/j.jagp.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Functional Connectivity Features in Grief: A Pilot Longitudinal Study

Abstract: Objective.-Acute grief, in an important minority of older adults, can become protracted, intense, and debilitating, leading to the development of complicated grief (CG). However, the neurobiological mechanisms underlying a maladaptive grief response after an attachment loss are unknown. The current study aimed to examine the amygdala brain network features that crosssectionally explain the symptom variance and longitudinally relate to grief symptom trajectories after an attachment loss.Methods.-Baseline amygda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Their results showed that MCI reduced the positive amygdala FC with parieto-occipital regions, insula, and hippocampus; mild AD patients reduced the amygdala FC mainly in the medial temporal and insular regions (55). These studies show that the severity of symptoms is the result of multiple neural network changes, not necessarily parallel to a single network change (56)(57)(58). This may be one of the reasons why we did not find a correlation between the amygdala-FC and neuropsychological performance.…”
Section: Discussionmentioning
confidence: 58%
“…Their results showed that MCI reduced the positive amygdala FC with parieto-occipital regions, insula, and hippocampus; mild AD patients reduced the amygdala FC mainly in the medial temporal and insular regions (55). These studies show that the severity of symptoms is the result of multiple neural network changes, not necessarily parallel to a single network change (56)(57)(58). This may be one of the reasons why we did not find a correlation between the amygdala-FC and neuropsychological performance.…”
Section: Discussionmentioning
confidence: 58%
“…There is evidence that amygdala responses to sad stimuli are higher without cognitive reappraisal and involvement of the dorsolateral prefrontal cortex (59). In addition, individuals with complicated or recent grief have elevated amygdala reactivity to sadness (60) and stronger connections between the amygdala and regions involved in autobiographic memory (61).…”
Section: Behavioral and Neural Alterations Related To Early Adversitymentioning
confidence: 99%
“…In a recent longitudinal study, bereaved adults who displayed greater amygdala functional connectivity with salience and executive control networks experienced worsening grief symptoms over time. Cross‐sectionally, higher prolonged grief symptoms were associated with greater amygdala functional connectivity with posterior default network regions (Chen et al, 2020 ). Further, treatment‐seeking bereaved adults who received 8 weeks of mindfulness‐based cognitive therapy showed decreased resting state functional connectivity between salience, default, and executive control networks (Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%